Decision making in Ultimatum Game - Avanesyan, Galina; Zouhar, Jan, 1982-; Dlouhý, Martin, 1970-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2014)
The aim of this work is to show that even people who outwardly demonstrate irrational behaviour are actually rational. The only reason why their actions deviate from theoretical rational behaviour is given by different utility functions. Ultimatum game with its easy rules represents a great way to show deviations between human and rational behaviours. The model described in the thesis focuses on Responder's decision making, which is influenced not only by maximization of pure economical profit but also by many other factors, which are summed in the model in one variable -- attitude to fairness. It is shown how this variable can be predicted using decisions obtained from a multi-round Ultimatum game. To prove that humans behave in accordance with their own preferences, the modelled game does not only estimate players' attitudes to fairness but also predicts players' following actions using knowledge of estimated values.
Vedoucí práce: Jan Zouhar
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses